Boron-chalcogen heterocycles and linear tetraboranes from a cyclic tetra(amino)tetraborane - Eva Beck; Diana Bröllos; Ivo Krummenacher; Thomas Kupfer; Maximilian Dietz; Tim Wellnitz; Cornelius Mihm; Holger Braunschweig (Nature Communications)
Abstract While small carbocyclic rings have long been recognized as pivotal building blocks in chemistry, their all-boron counterparts have remained largely unexplored. In this work, we present a detailed account of the functionalization reactivity of our cyclic tetraborane B4(NCy2)4 (Cy = cyclohexyl) encompassing both ring-expansion and ring-opening reactions. Specifically, diphenyl dichalcogenides effect ring expansion to five-membered B4E rings (E = S, Se, Te), while halogenating agents induce ring opening to generate linear tetraboranes with halide end groups. These transformations reveal reactivity patterns reminiscent of strained organic ring systems, thus highlighting the cyclic tetraborane’s potential as a versatile precursor for synthesizing intricate boron-rich architectures.